RELIGION, WILLIAM E . PADEN DAN KEBERAGAMAAN DI INDONESIA - AINUL CHURRIA ALMALACHIM (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2020)
This paper examines how to view the religion of William E. Paden's perspective in his work entitled